Roselle Calyx Powder Can Increase Total Gas Production, without affecting pH, Methane, and Dry Matter and Organic Matter Degradability - Azhar, Khaerul; Ramdani, Diky; Hernaman, Iman (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
Roselle calyx powder (RCP) can act as natural dietary additives in a concentrate. A completely randomized design was employed in this study to determine the impact of 6 different doses of RCP supplementation (0, 0.1, 0.2, 0.4, 0.8, and 1.6%) in a rice straw-based diet using 6 replicates (n = 6) on in vitro dry matter degradability (IVDMD), in vitro organic matter degradability (IVOMD), pH, total gas production 8 hours (TGP8), total gas production 16 hours (TGP16), total gas production 24 hours (TGP24) and methane. RCP supplementation did not affect the degradability, pH, and methane. The lower dose of RCP-0.1 supplementation obtained greater TGP than the higher doses, increased TGP can be a sign of increasing rumen fermentation process. However, higher doses RCP are not recommended, as the bioactive compounds may act as antinutrients, inhibiting the fermentation process.